Discovery of talmapimod analogues as polypharmacological anti-inflammatory agents - Wandong Liu; Caiyun Hou; Jiaming Li; Xiaodong Ma; Yanchun Zhang; Mengqi Hu; Yuanzheng Huang (Taylor & Francis Group, 2020)
Twenty novel talmapimod analogues were designed, synthesised and evaluated for the in vivo anti-inflammatory activities. Among them, compound 6n, the most potent one, was selected for exploring the mechanisms underlying its anti-inflammatory efficacy. In RAW264.7 cells, it effectively suppressed lipopolysaccharides-induced (LPS-induced) expressions of iNOS and COX-2. As illustrated by the western blot analysis, 6n downregulated both the NF-κB signalling and p38 MAPK phosphorylation. Further enzymatic assay identified 6n as a potent inhibitor against both p38α MAPK (IC50=1.95 µM) and COX-2 (IC50=0.036 µM). By virtue of the concomitant inhibition of p38α MAPK, its upstream effector, and COX-2, along with its capability to downregulate NF-κB and MAPK-signalling pathways, 6n, a polypharmacological anti-inflammatory agent, deserves further development as a novel anti-inflammatory drug.